Electrocatalytic Oxygen Reduction on Transition Metal Macrocyclic Complexes for Anion Exchange Membrane Fuel Cell Application - Zagal-Moya, J; Zagal-Moya, J (Elsevier B.V., 2018)
This review discusses the electrocatalytic activity of MN4 macrocyclic complexes for the O2 reduction reaction. The main reactivity descriptors for these complexes, essentially the M(III)/(II) redox potential and the M–O2 binding energies are considered. MNx pyrolysed catalysts are only discussed briefly as this will be covered in other articles of this issue. The performance of these catalysts in anion exchange membrane fuel cell (AEMFC) is thoroughly reviewed. © 2018 Elsevier B.V.